MANAGEMEN PENDIDIKAN DALAM UPAYA PENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MI MIFTAHUL ULUM - Wahyu Fiananda; Slamet Widodo (Journal of Professional Elementary Education, 2023)
The quality of education is low, resulting in schools having to create ways to overcome this. School management is everything related to the management of the educational process to achieve the goals that have been set, both short-term goals, medium-term goals, and long-term goals. The purpose of this study was to determine school management in improving the quality of education, including: (1) school profile; (2) School programs and (3) Teachers and Students. Data collection techniques were carried out through interview guidelines, observation guidelines, and documentation studies. The research subjects were the principal, supervisor and teacher at MI Miftahul Ulum. The results of the research found: (1) School program planning includes: teaching programs, including: school profiles, school programs, school organizational structure, school vision and mission, extracurricular activities, etc. It is expected that supervisors can direct and supervise school principals in improving the quality of education regarding school program planning, program implementation and the obstacles they face in an effective, effective and efficient manner so that the quality of education in these schools can be improved